Carbon Emission Reduction Potential of In-Place Pavement Recycling in Urban Coastal Road Maintenance - A Case Study of Hai Phong City - Nguyễn, Phan Anh; Cao, Thị Hồng Hạnh (Journal of Transportation Science and Technology, 2026)
This study applies life cycle assessment (LCA) to compare carbon emissions from milling and overlay with hot mix asphalt (M&O) and cold in-place recycling (CIR) for coastal urban roads in Hai Phong City. The functional unit is a 1 km Î 10 m road section over a 20-year period.Results show that total emissions of M&O range from 122 to 262 tCO2, while CIR varies between 29 and 237 tCO2 depending on system boundaries. On an area-based, on-site emission basis, CIR achieves a 76.4% reduction compared with M&O, particularly under coastal climatic conditions.Sensitivity analysis identifies cement and bitumen contents as key drivers of CIR carbon performance. Overall, CIR is a promising maintenance option supporting green transport infrastructure and Vietnam’s Net Zero 2050 target
Keywords: Cold in-place recycling; Carbon emission reduction; Life cycle assessment; Pavement maintenance; Coastal roads; Fatigue life extension